The Beryllium-7, 7Be depth penetration in two seasons study at Timah Tasoh, Perlis - Sharib@Sarip Jalal (Tanjung Malim, 2021)
The Beryllium-7, 7Be depth penetration in two seasons study at Timah Tasoh, Perlis by Sharib@Sarip Jalal